An ecological study of publicly funded elective hip arthroplasties in Brazil and Scotland: do access inequalities reinforce the inverse care law?. Issue 5 (May 2020) - Filippon, Jonathan; Bremner, Stephen; Giovanella, Ligia; Pollock, Allyson
Objectives: To compare elective hip arthroplasty rates funded by the public sector in Brazil and Scotland. Design: Ecological study, 2009–13, of crude and directly standardised rates of elective primary hip arthroplasty rates (per 100, 000) funded by the public sector at national and regional level for age (30 + years) and gender in Brazil and Scotland. Setting: National Health Service Scotland and Unified Health System in Brazil. Participants: Over 30 s who had undergone an elective hip arthroplasty funded by the public sector. Main outcome measures: Publicly funded standardised elective hip arthroplasty rates in Brazil and Scotland. Results: Between 2009 and 2013, there was a seven-fold difference in treatment rates between Brazil and Scotland, and an eight-fold regional difference in Brazil; Brazil (7.8–8.3/100, 000, increase of 0.5 per 100, 000, 95% confidence interval (CI) (0.3, 0.7) from 2009/10 to 2012/13) and Scotland (from 61.1 to 57.7/100, 000, decrease of 3.4 per 100, 000, 95% confidence interval (1.4, 5.8) per 100, 000); a two-fold difference in number of public beds per head of population (Brazil 158.3/100, 000 vs. Scotland 305.1/100, 000) and general medical workforce (Brazil 198.8/100, 000 vs. Scotland 327.4/100, 000); numbers of orthopaedic surgeons per head of population in the two countries were similar in 2013 (Brazil 5.2/100, 000 vs. Scotland 4.3/100, 000). Conclusion: Although the 'inverse care law' is seen in both countries, access to publicly funded hip arthroplasties in Brazil is worse than in Scotland; the distribution of specialists and higher treatment rates in Brazil is highly skewed towards wealthier areas, perpetuating historical regional inequalities.